Evaluation of two commercial kits and two laboratory-developed qPCR assays compared to LAMP for molecular diagnosis of malaria - Azza Bouzayene; Rizwana Zaffaroullah; Justine Bailly; Liliane Ciceron; Véronique Sarrasin; Sandrine Cojean; Nicolas Argy; Sandrine Houzé; Valentin Joste; the French National Malaria Reference Centre study group (Malaria Journal, 2022)
Abstract Background Malaria is an infectious disease considered as one of the biggest causes of mortality in endemic areas. This life-threatening disease needs to be quickly diagnosed and treated. The standard diagnostic tools recommended by the World Health Organization are thick blood smears microscopy and immuno-chromatographic rapid diagnostic tests. However, these methods lack sensitivity especially in cases of low parasitaemia and non-falciparum infections. Therefore, the need for more accurate and reliable diagnostic tools, such as real-time polymerase chain reaction based methods which have proven greater sensitivity particularly in the screening of malaria, is prominent. This study was conducted at the French National Malaria Reference Centre to assess sensitivity and specificity of two commercial malaria qPCR kits and two in-house developed qPCRs compared to LAMP. Methods 183 blood samples received for expertise at the FNMRC were included in this study and were subjected to four different qPCR methods: the Biosynex Ampliquick® Malaria test, the BioEvolution Plasmodium Typage test, the in-house HRM and the in-house TaqMan qPCRs. The specificity and sensitivity of each method and their confidence intervals were determined with the LAMP-based assay Alethia® Malaria as the reference for malaria diagnosis. The accuracy of species diagnosis of the Ampliquick® Malaria test and the two in-house qPCRs was also evaluated using the BioEvolution Plasmodium Typage test as the reference method for species identification. Results The main results showed that when compared to LAMP, a test with excellent diagnostic performances, the two in-house developed qPCRs were the most sensitive (sensitivity at 100% for the in-house TaqMan qPCR and 98.1% for the in-house HRM qPCR), followed by the two commercial kits: the Biosynex Ampliquick® Malaria test (sensitivity at 97.2%) and the BioEvolution Plasmodium Typage (sensitivity at 95.4%). Additionally, with the in-house qPCRs we were able to confirm a Plasmodium falciparum infection in microscopically negative samples that were not detected by commercial qPCR kits. This demonstrates that the var genes of P. falciparum used in these in-house qPCRs are more reliable targets than the 18S sRNA commonly used in most of the developed qPCR methods for malaria diagnosis. Conclusion Overall, these results accentuate the role molecular methods could play in the screening of malaria. This may represent a helpful tool for other laboratories looking to implement molecular diagnosis methods in their routine analysis, which could be essential for the detection and treatment of malaria carriers and even for the eradication of this disease.